Hepatitis B testing and access to care among racial and ethnic minorities in selected communities across the United States, 2009‐2010. Issue 3 (6th August 2013) - Hu, Dale J.; Xing, Jian; Tohme, Rania A.; Liao, Youlian; Pollack, Henry; Ward, John W.; Holmberg, Scott D.
<x xml:space="preserve">Abstract</x> Hepatitis B virus (HBV) infection is widely prevalent among racial and ethnic minorities in the United States; however, few data have been available regarding HBV testing and referral to care for these populations. Using survey data collected in 2009‐2010 from the Racial and Ethnic Approaches to Community Health (REACH) across the U.S., we assessed rates and determinants of hepatitis B testing and access to care in 28 minority communities in the U.S. Of 53, 896 respondents, 21, 129 (39.2%) reported having been tested for hepatitis B. Of the 1, 235 who reported testing positive, 411 (33.3%) reported currently receiving specialty care. After controlling for demographic and socioeconomic characteristics, the likelihood of having been tested for hepatitis B and receiving care if infected was higher among males, non‐English speaking persons, and those having health insurance compared to their counterparts. Compared to college graduates, respondents without a college education were less likely to get tested for hepatitis B. Conclusion: These data indicate that more than half of racial/ethnic minority persons in these communities had not been tested for hepatitis B, and only about one‐half of those who tested positive had ever received treatment. More state and federal efforts are needed to screen racial/ethnic minorities, especially foreign‐born persons, for HBV and link those with infection to care. (Hepatology 2013;53:856–862)